Novel technique for comminuted patellar fixation using suture tape in spiderweb configuration - Tee, Wei Jie; Yeo, Kuei Siong Andy; Chua, David Thai Chong; Moo, Ing How (Frontiers in Surgery, 2024)
IntroductionPatella fractures account for 1% of skeletal fractures in orthopedic surgery. Simple two-part patella fractures are uncommon; most fractures are comminuted with significant articular involvement. Traditionally, patella fractures have been fixed using a tension band technique with cerclage wire, which has several complications including soft-tissue irritation, implant migration, and breakage, leading to secondary implant removal in up to 37% of patients. Newer fixation methods using cannulated screws, hook plates, mesh plates, and locking plates show promise but are costly and require extensive soft-tissue dissection. There is a need for a better alternative, especially for the elderly with osteoporotic bones.Recent developmentsVarious authors have described patellar fixation techniques augmented with sutures and suture tape, showing satisfactory outcomes. This paper proposes a novel all-suture tape method for patellar fixation, suitable for common types of patella fractures including AO 34C1.1 (transverse), AO 34C2 (transverse and split), and 34C3 (comminuted). Suture tape is biomechanically superior in both soft tissue and bone.Operative techniqueThe patient is laid supine with the knee in full extension. A standard anterior midline approach is adopted. After reducing the fracture fragments and securing them with K-wires, non-absorbable suture tapes are used instead of cerclage wire. The tapes are passed multiple times through the soft tissue, creating loops that are then tensioned to compress the fracture fragments. The technique is completed by creating a tension band fixation with additional suture tapes.Expected outcomesThis technique offers several benefits, including reduced operative time, minimized soft-tissue dissection, and lower risk of implant prominence and irritation. The suture tape's superior tensile strength and low tissue reactivity reduce complications and the need for secondary surgeries. Early results from two cases show union achieved at 3 months without complications, with patients regaining full range of motion.ConclusionThis preliminary technical paper demonstrates the feasibility of using non-metallic implants for patella fracture fixation. The proposed method shows promising results, suggesting a potential shift in the approach to fracture fixation. Further research and larger cohort studies are needed to validate these findings.